2003
DOI: 10.1046/j.1365-313x.2003.01738.x
|View full text |Cite
|
Sign up to set email alerts
|

Ku80‐ and DNA ligase IV‐deficient plants are sensitive to ionizing radiation and defective in T‐DNA integration

Abstract: SummaryDouble-strand break (DSB) repair pathways catalyze the rejoining of broken chromosomes and the integration of transforming DNAs. These processes have been well characterized in bacteria, fungi, and animals. Plants are generally thought primarily to utilize a non-homologous end joining (NHEJ) pathway to repair DSBs and integrate transgenes, as transforming DNAs with large tracts of homology to the chromosome are integrated at random. In order to test the hypothesis that NHEJ is an important pathway for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(150 citation statements)
references
References 50 publications
(57 reference statements)
5
142
2
1
Order By: Relevance
“…There are conflicting reports about the role of KU80 in T-DNA integration. Gallego et al (2003) found no deficiency in T-DNA integration in Arabidopsis ku80 mutants, whereas Friesner and Britt (2003) showed a reduction in T-DNA integration in Arabidopsis ku80 mutants. Subsequently, Li et al (2005) showed that Arabidopsis ku80 mutants showed decreased stable transformation, whereas Ku80 overexpression showed increased T-DNA integration and increased resistance to methyl methanesulfonate (MMS).…”
Section: Introductionmentioning
confidence: 89%
“…There are conflicting reports about the role of KU80 in T-DNA integration. Gallego et al (2003) found no deficiency in T-DNA integration in Arabidopsis ku80 mutants, whereas Friesner and Britt (2003) showed a reduction in T-DNA integration in Arabidopsis ku80 mutants. Subsequently, Li et al (2005) showed that Arabidopsis ku80 mutants showed decreased stable transformation, whereas Ku80 overexpression showed increased T-DNA integration and increased resistance to methyl methanesulfonate (MMS).…”
Section: Introductionmentioning
confidence: 89%
“…It has been shown recently that these difficulties may be caused by the existence of independent end-joining pathways in plant cells (Charbonnel et al, 2011). A mild reduction in T-DNA transformation efficiencies was reported when single NHEJ factors were knocked out, but no GT experiments have yet been published concerning this issue (Friesner and Britt, 2003;Nishizawa-Yokoi et al, 2012).…”
Section: Manipulation Of the Enzyme Machinery Can Help (A Bit)mentioning
confidence: 99%
“…Mutants in DNA repair/maintenance genes in Arabidopsis, such as DNA ligase IV, ERCC1, and telomerase, do not exhibit obvious cell death, even in response to treatment with DNA damaging agents (Riha et al, 2001;Friesner and Britt, 2003;Hefner et al, 2003). A prevailing hypothesis is that plants, which have no p53 homolog, lack DNA damage-induced cell death (apoptosis).…”
Section: Atatr Responses To Replication Blocksmentioning
confidence: 99%